2021
DOI: 10.3389/fnagi.2021.632138
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Can Effectively Predict Early Hematoma Expansion of Intracerebral Hemorrhage Analyzing Noncontrast Computed Tomography Image

Abstract: This study aims to develop and validate an artificial intelligence model based on deep learning to predict early hematoma enlargement (HE) in patients with intracerebral hemorrhage. A total of 1,899 noncontrast computed tomography (NCCT) images of cerebral hemorrhage patients were retrospectively analyzed to establish a predicting model and 1,117 to validate the model. And a total of 118 patients with intracerebral hemorrhage were selected based on inclusion and exclusion criteria so as to validate the value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Recent studies have shown that quantitative NCCT markers can be used to predict hematoma expansion [ 42 , 43 ]; however, the need for specialist software may limit the widespread use of this technique. In addition, the artificial intelligence model offers improved specificity and sensitivity in predicting HE [ 44 ]. In conclusion, predicting HE using NCCT images is a promising prospect.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that quantitative NCCT markers can be used to predict hematoma expansion [ 42 , 43 ]; however, the need for specialist software may limit the widespread use of this technique. In addition, the artificial intelligence model offers improved specificity and sensitivity in predicting HE [ 44 ]. In conclusion, predicting HE using NCCT images is a promising prospect.…”
Section: Discussionmentioning
confidence: 99%
“…The study included 261 patients, eventually reaching an AUC of 0.867 in the validation cohort. A deep learning method was developed and validated to predict HE in patients with intracerebral hemorrhage [ 32 ]. The investigators retrospectively analyzed 1899 non-contrast computed tomography (NCCT) images of 118 patients with intracerebral hemorrhage and established a prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…The deep learning system was developed by involving 1771 hypertensive intracerebral hemorrhage patients from 84 hospitals spread among 9 provinces and 25 cities, all of which were members of the Chinese Stroke Center Alliance. The proposed model achieved a sensitivity and specificity of 89.3% and 81.1% for hematoma expansion [ 26 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies used AI to predict hematoma expansion in HICH patients. One previous study reported a hematoma prediction AI model which provided a time-saving, easy to implement, and subjective and independent method to predict the risk of hematoma enlargement in patients with intracerebral hemorrhage based on the NCCT images [ 26 ]. This study aimed to explore the value of the deep learning algorithm for the prediction of hematoma expansion from NCCT scans through external validation.…”
mentioning
confidence: 99%